Konsepsi Berprestasi secara Akademik Mahasiswa: Kasus Mahasiswa Program Studi D-II PGSD - Nabisi Lapono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
This qualitative research was conducted to examine the variety of cultural values among students of D-II PGSD which shaped their conception of academik achievement. The results of interviews and observations suggest that there was no difference in conception of academik achievement among students from different ethnic groups. In addition, students' motivation to succeed went beyond their academik boundaries. These findings imply the need for designing and implementing programs for quality human resource development.